Groundwater potentiality and evaluation in the Egyptian Nile Valley: case study from Assiut Governorate using hydrochemical, bacteriological approach, and GIS techniques - Megahed, H.A. (2021)
We analyzed 92 samples collected from shallow boreholes within 15 km on both sides of the River Nile for major, minor, and trace ions and compared the results to the national and international standards for drinking water. Some chemical data were collected from Assiut Drinking Water Station while some other samples were analyzed chemically and bacteriological in the Laboratories of Science and agriculture faculties and the laboratories of Assiut Drinking & sanitation Company. The groundwater composition is seasonally variable depending on the variation in the local surface water (level composition). The results of bacteriological examination show that the highest most probable number of total coliform was found 5.9 MPN/100 ml and the minimum value of MPN of total coliform was found 1.1 MPN/100 ml. Groundwater potentiality and evaluation for drinking and domestic uses depend on several parameters which must be taken into consideration.